Text structures affect reading speed / Shauqiah Jufri, Noor Halilah Buari and Ai-Hong Chen - Jufri, Shauqiah; Buari, Noor Halilah; Chen, Ai-Hong (Penerbit UiTM (UiTM Press), 2016)
The objective of this study was to investigate how the text structures affect reading speed in the same participants. Two types of text structures were used. The first text structure (TS1) had a total of 84 words that formed by 14 separate sentences with 6 words in each sentence (3-words per line). The second text structure (TS2) was written as 100-words passage with 10 continuous sentences. The average words in TS2 was 3 to 15 words per sentence. The sentences were constructed in Malay language and words selected from Malay textbook under The Malaysia Ministry of Education (MMOE). Twenty-five participants were asked to read aloud both text structures at random. Time to complete both texts was measured with stopwatch and recorded using audiotape. The error was noted in recording sheet if there were any omission, repeated, added or misread of word. Reading speed was calculated as words per minute (wpm). Mean reading speed in for TS1 was found to be faster than TS2 (t=10.61, p<0.01). In conclusion, text structures might affect reading speed among Malay-native speakers. Therefore, it was importance to consider about the text structure in designing the reading material for evaluation and monitoring the reading and vision rehabilitation.